Simulation and Modeling Related to Computational Science and Robotics Technology: Proceedings of SiMCRT 2011 - Kojima, Fumio (IOS Press, 2014)
This volume includes a selection of papers presented at the International Workshop on Simulation and Modeling related to Computational Science and Robotics Technology (SiMCRT2011) was organized by Kobe University during November 1–3, 2011 at the Takikawa Memorial Hall, Kobe University Japan. This workshop was also cosponsored by AFOSR/AOARD under Grant No. FA23861111041. Historically, this workshop was the third international meeting for providing a forum for discussing recent developments in the growing field of engineering science and mathematical sciences. The first workshop took place in 1997 in Osaka Institute of Technology, Osaka, Japan.